Islamic Pre-School Management and Its Implications towards Students’ Learning Quality Improvement - Rosniati Hakim (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
Islamic education in schools had not completely assessed the development of students’ character and personality. Therefore, additional religious education through non-formal education and religious practices were needed in Islamic Pre-Schools. It provided a forum to foster, develop, cultivate, and transform the religious value of the students to improve their personality. The purpose of this research was to examine social phenomenon that occur naturally through the facts related to management activities of students. Qualitative research was used in this study where the data taken from head of Islamic pre-school and the school deputy, teacher, staffs, mosque administrators of Baitul Haadi, administrator of the school, staffs of Ministry of Religious Affairs as well as Islamic pre-school inspectors, parents, community leaders, and administrators of professional organizations. The finding showed that students’ management applied in Islamic pre-school through the management functions is able to provide the successful of student’s education and learning implementation. It was also found that student management applied in Islamic pre-school is planning activities of students’ admission process through the administration regularly with various regulations related to the success of education. Thus, it is expected that the government will provide the guidance and implement constant supervision in accordance with applicable regulations.